Pengaruh Brand Image dan Harga terhadap Keputusan Pembelian Smartphone Realme: Studi Kasus pada Wilayah Kabupaten Subang - Regie Ardiansa; Salim Siregar (Jurnal Maksipreneur, 2022)
The advancement of information and communication technology is increasing rapidly causing the public's need for smartphone products to increase. The purpose of this study was to analyze the correlation between brand image and price on purchasing decisions for Realme smartphones in Subang Regency, West Java. This research uses a descriptive and quantitative verification approach. The sample used in this study amounted to 303 consumers as respondents which were determined by using the accidental sampling technique. The data analysis method used in this research is collecting data using a questionnaire instrument with a Likert scale. The results of this study are brand image and price have a strong and positive relationship. Furthermore, this study also found that brand image and price have significantly and positively affected purchasing decisions for Realme smartphone products in Subang Regency.